Bilingual Education in China Practices, Policies and Concepts - Feng, Anwei (Bilingual Education & Bilingualism, 2007)
The complexity and diversity of the linguistic situations, practices, policies and theories of bilingual education is widely acknowledged in a country with a population of 1.3 billion people consisting of 56 officially recognised indigenous nationalities speaking more than 80 languages. This book addresses this complexity and diversity with a comprehensive examination of issues in bilingual education for both minority and majority nationalities in China and explores the links between the two major forms of bilingual education. It includes voices that are ‘emic’ or ‘etic’, local or international, and voices that come from those who work at the forefront of bilingual education or in the development of theory. All these voices are needed as different and divergent perspectives represent a reality